(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The concept of green infrastructure and ecological urban planning has become one of the leading directions in achieving sustainable development, environmental balance, and socio-economic well-being in the 21st century. As rapid urbanization continues across the globe, cities are facing severe environmental challenges such as air and water pollution, inefficient energy consumption, and climate-related risks. In this context, green infrastructure serves as a comprehensive approach to integrate natural systems into urban environments, providing ecological services such as clean air, green transportation, biodiversity protection, and climate adaptation.